Analysis of complications following vaginal hysterectomy in pelvic organ prolapse - RC, Laxmi; Das, Chitra Ranjan (Journal of Kathmandu Medical College, 2016)
Background: Vaginal hysterectomy is one of the most common gynecological procedures performed in Nepal. The most common indication is pelvic organ prolapse (POP). The common complications associated with vaginal hysterectomy are hemorrhage, infections and injury to adjacent organs.Objectives: The aim of this study was to study the type of complications following vaginal hysterectomy in pelvic organ prolapse.Methods: A Prospective observational study was carried out at Lord Buddha Educational Academy Nepalgunj Medical College, Kohalpur, Banke, Nepal from November 2008 to May 2009. A total of 311 patients belonging to age group (20-80) years, presenting to the out-patient department with second to fourth degree utero-vaginal prolapse without any severe medical and surgical problems were included in this study. All the patients who had undergone vaginal hysterectomy during the study period and met the inclusion criteria were included in this study. The data collected was analyzed with standard statistical method (SPSS statistics 16.0).Results: Total of 311 women were included in this study between the age group (20-80 years) with pelvic organ prolapsed (second to fourth degree). All of them underwent vaginal hysterectomy. Among them 39 (12.5%) had complications. The most common complication was secondary haemorrhage accounting for eleven (28.2%) of all complications. Eight (20.5%) patients had retention of urine, four (10.3%) had headache, three (7.7%) patients had primary haemorrhage, three (7.7%) had pelvic cellulitis, three (7.7%) had UTI, three (7.7%) vault abscess, one (2.6%) had bladder injury, one (2.6%) had pelvic peritonitis, one (2.6%) had vault prolapse. We had one death due to septicemia following seven days of post operation.Conclusion: In our study, complication of vaginal hysterectomy was 39 (12.5%) out of 311 patient. The most common complication being secondary haemorrhage 11 (28.2%).Journal of Kathmandu Medical College, Vol. 4(1) 2015, 12-15